Effects of incubation temperature and maternal phenotype on Baltic herring (Clupea harengus membras) eggs and larvae: An experimental study - Mäkinen Katja; Rajasilta Marjut; Ruuskanen Suvi; Karpela Tiia; Lauerma Aarne; Sahlstén Johannes (Canadian Science Publishing, 2025)
Temperature modifies the reproductive success of fish, yet, in many species, we lack the information on its role in the early development. In this study, the effect of temperature on the relation between maternal traits (length, age, somatic condition, and muscle lipid and ovarian thyroid hormone concentrations), egg quality (fertilization success, development rate, mortality, and hatching success), and offspring traits (size-at-hatch, yolk sac size, and proportion of malformations) were studied in Baltic herring (Clupea harengus membras) in the northern Baltic Sea. The experiments were conducted at an ambient temperature of 7 °C and at an elevated temperature of 14 °C using 5 to 10 females and 3 replicates per female. The results indicate that elevated temperature may result in a faster developmental rate, a lower early-stage mortality and hatching success, smaller size-at-hatch, a larger yolk sac size, and a higher amount of larval malformations when compared to an ambient temperature. The egg and offspring traits were also associated with the maternal traits, indicating especially that thyroid hormones play a mediating role in the physiological processes.